2019
DOI: 10.3390/ma12223670
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Carrier Gases on the Quality of Epitaxial Corundum-Structured α-Ga2O3 Films Grown by Mist Chemical Vapor Deposition Method

Abstract: This report systematically investigates the influence of different carrier gases (O2, N2, and air) on the growth of gallium oxide (Ga2O3) thin films on c-plane sapphire substrates by using the mist-CVD method. Although XRD and Raman measurements show that the pure corundum-structured α-Ga2O3 with single (0006) plane orientation was successfully obtained for all three different carrier gases, the crystal quality could be greatly affected by the carrier gas. When O2 is used as the carrier gas, the smallest full-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 24 publications
5
12
0
2
Order By: Relevance
“…However, it is difficult to produce a β-Ga 2 O 3 wafer with a diameter large enough for practical application due to easy formation of cleavages such that the wafer size is limited to four inches [ 9 ]. Recently, mist chemical vapor deposition (Mist-CVD) has been introduced as a non-vacuum solution-process heteroepitaxy for α-Ga 2 O 3 on mass-produced sapphire (Al 2 O 3 ) wafers up to six inches, with a similar a crystal structure to α-Ga 2 O 3 [ 10 , 11 , 12 , 13 , 14 ]. Being able to lift α-Ga 2 O 3 off of the sapphire substrate and bond it to other substrates with high thermal conductivity (such as SiC, AlN, diamond, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to produce a β-Ga 2 O 3 wafer with a diameter large enough for practical application due to easy formation of cleavages such that the wafer size is limited to four inches [ 9 ]. Recently, mist chemical vapor deposition (Mist-CVD) has been introduced as a non-vacuum solution-process heteroepitaxy for α-Ga 2 O 3 on mass-produced sapphire (Al 2 O 3 ) wafers up to six inches, with a similar a crystal structure to α-Ga 2 O 3 [ 10 , 11 , 12 , 13 , 14 ]. Being able to lift α-Ga 2 O 3 off of the sapphire substrate and bond it to other substrates with high thermal conductivity (such as SiC, AlN, diamond, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Политип α-Ga 2 O 3 имеет структуру корунда и небольшую разницу в постоянных кристаллической решетки с сапфиром: 3.3% (c) и 4.5% (a) [9]. При этом α-Ga 2 O 3 обладает одной из самых больших шириной запрещенной зоны: E g = (5.1−5.3) эВ [10], что позволяет рассматривать его в качестве перспективного материала для создания солнечно-слепых детекторов в диапазоне глубокого УФ. В данной работе рассмотрено влияние структуры сапфировой подложки на электрические и фотоэлектрические характеристики слоев α-и ε-фаз оксида галлия.…”
Section: Introductionunclassified
“…This Special Issue is dedicated to these recent developments and contains 10 manuscripts reporting thin-film deposition and coating and their characterization. It compiles works on vapor-phase deposition processes including atomic-layer deposition (ALD) [ 1 , 2 ], mist-chemical-vapor deposition [ 3 ] and atmospheric-pressure chemical-vapor deposition (APCVD) [ 4 ] methods in which authors have studied the stabilization of metastable phases and the effect of growth conditions on thin film quality, epitaxy, and crystallinity. The Special Issue also includes liquid-phase coatings like sol-gel [ 5 ], solution immersion [ 6 ], micro-arc oxidation [ 7 ], Plasma Electrolytic Oxidation Processing [ 8 ], and single pulse anodization [ 9 ] where the authors were more focused on the coating of aluminum.…”
mentioning
confidence: 99%
“…They showed that crystal orientations of the films can be tuned by the selection of the substrate and mitigated through the interface via solid-face epitaxy upon annealing. In the third manuscript, Xu et al report on the influence of carrier gases in mist chemical vapor deposition method on the quality of epitaxial corundum-structured α-Ga 2 O 3 films [ 3 ]. The thin films were grown on c-plane sapphire substrates with single (0006) plane orientation for all carrier gases, but the authors demonstrated that the O 2 gas enables the growth of better quality epitaxial films with increased growth rate (10.3 nm/min vs. 5.3 nm/min and 2.4 nm/min) and better crystalline quality.…”
mentioning
confidence: 99%